Use of serious games in medicine: a literature revision (Research, Society and Development, 2021)
It is noticeable that more and more medical professionals have been searching for strategies to keep people engaged both in the recovery processes (cognitive or physical) and in the teaching part. It is possible to observe that the insertion of Serious Games has been offering this innovative possibility, which allows the development of new possibilities for several areas of knowledge. This study aims to carry out a review on the use of Serious Games in Medicine, exploring how the method has been used. The methodology used was a systematic review. Articles published from 2015 to 2020 in indexed in three databases such as IEEE, Scopus, Scielo, among others, were searched. If used correctly, the Serious Games can help in the rehabilitation process of patients affected by some sequelae caused by stroke (CVA - Cerebral Vascular Accident), and also in the rehabilitation process of people with degenerative problems. It was also possible to observe that SG can be used as motivating and engaging tools for medical students.